Estimates of glomerular filtration rate in the critically ill with sepsis - Md Ralib, Azrina; Dzaharudin, Fatimah; Mat Nor, Mohd Basri (Elsevier BV, 2017)
Accurate assessment of glomerular filtration rate (GFR) in ICU patients is very important for institution of supportive therapy, preventive therapy, early renal support, drug dosing modification or avoidance of nephrotoxic drugs. Kinetic estimate of GFR (keGFR) takes into account the changes of creatinine over time, creatinine production rate, and the volume of distribution, hence postulated to be a more accurate estimate of GFR in the acute setting, where there are rapidly changing kidney functions as in the critically ill. We evaluated the association of the keGFR with estimated GFR (eGFR) by conventional method.